Iron deficiency increases blood concentrations of neurotoxic metals in children - Yangho Kim; Sangkyu Park (Korean Pediatric Society, 2014)
Iron deficiency affects approximately one-third of the world's population, occurring most frequently in children aged 6 months to 3 years. Mechanisms of iron absorption are similar to those of other divalent metals, particularly manganese, lead, and cadmium, and a diet deficient in iron can lead to excess absorption of manganese, lead, and cadmium. Iron deficiency may lead to cognitive impairments resulting from the deficiency itself or from increased metal concentrations caused by the deficiency. Iron deficiency combined with increased manganese or lead concentrations may further affect neurodevelopment. We recently showed that blood manganese and lead concentrations are elevated among iron-deficient infants. Increased blood manganese and lead levels are likely associated with prolonged breast-feeding, which is also a risk factor for iron deficiency. Thus, babies who are breast-fed for prolonged periods should be given plain, iron-fortified cereals or other good sources of dietary iron.